The rhetoric of transformation in the healing of alcoholism: The twelve steps of alcoholics anonymous - Swora, Maria Gabrielle (Mental health, religion & culture, 2004)
Close attention to spirituality and change are necessary for a fuller understanding of how Alcoholics Anonymous (AA) works. This paper draws upon the conceptual tools of the anthropology of religious healing to interpret AA's program for recovery, the Twelve Steps. The Twelve Steps are described as a fundamental component of AA discourse, and as a rhetoric of transformation. The Twelve Steps outline a rhetorical process which moves the alcoholic from drinking to sobriety by means of a rhetoric of predisposition, of empowerment, and of transformation. AA discourse is spiritual, in that members are persuaded to interpret the world, their lives, and their affliction in sacred terms. Healing is not cure, but a new way of attending to the world and engaging with others, including God, or a ‘Power greater than ourselves’. There is a God, and it's not me. Let go and Let God. I had to change. The same person would drink again. - Three Alcoholics Anonymous slogans